A Novel Preparation Technique for Human Nasal Respiratory Mucosa to Disclose Its Glycosylation Pattern for Bioadhesive Drug Delivery - Julia Clara Gausterer; Michael Schlager; Navid Ahmadi; Michael Nieratschker; Valerie Dahm; Michael Wirth; Christoph Arnoldner; Clemens Honeder; Franz Gabor (MDPI AG, 2023)
To shed some light on glycotargeting as a potential strategy for nasal drug delivery, a reliable preparation method for human nasal mucosa samples and a tool to investigate the carbohydrate building blocks of the glycocalyx of the respiratory epithelium are required. Applying a simple experimental setup in a 96-well plate format together with a panel of six fluorescein-labeled lectins with different carbohydrate specificities allowed for the detection and quantification of accessible carbohydrates in the mucosa. As confirmed by binding experiments at 4 °C, both quantitatively by fluorimetry and qualitatively by microscopy, the binding of wheat germ agglutinin exceeded that of the others by 150% on average, indicating a high content of N-acetyl-D-glucosamine and sialic acid. Providing energy by raising the temperature to 37 °C revealed uptake of the carbohydrate-bound lectin into the cell. Moreover, repeated washing steps during the assay gave a slight hint as to the influence of mucus renewal on bioadhesive drug delivery. All in all, the experimental setup reported here for the first time is not only a suitable approach to estimating the basics and potential of nasal lectin-mediated drug delivery but also meets the needs for answering a broad variety of scientific questions involving the use of ex vivo tissue samples.